(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the current state of knowledge and practices regarding medical solid waste management among healthcare staff at Hai Duong Medical Center in 2025. Method: Cross-sectional descriptive study with analysis. Results: The results show that the percentage of staff with general knowledge of medical solid waste management is 76.0%. Of this, knowledge of medical solid waste classification is the highest (91.3%), followed by knowledge of collection at the lowest (58.0%); general practices in medical solid waste management are 90.7%. Multivariate analysis results show that: professional title and participation in training are related to knowledge attainment (statistically significant p<0.05); the factors of administrative work and general knowledge attainment are related to practice attainment in medical solid waste management (with p<0.05). Conclusion: The percentage of subjects with satisfactory knowledge of medical solid waste management was 76.0%, and those with satisfactory practice was 90.7%; Factors related to knowledge included two factors: professional title and participation in training; and two factors, administrative staff and knowledge, were correlated with overall satisfactory practice, with statistically significant differences (p<0.05).